IDENTIFYING A “CHICAGO SCHOOL” OF ECONOMICS: ON THE ORIGINS, DIFFUSION, AND EVOLVING MEANINGS OF A FAMOUS NAME BRAND - Medema, Steven G. (Journal of the History of Economic Thought, 2024)
Though the Chicago school has been the subject of no small amount of research over the past several decades, that scholarship has focused largely on persons, ideas, and influence—in short, on the school itself. No attention has been paid to the origins of that label and the avenues via which the notion of a “Chicago school” of economics came to be. This paper attempts to address that lacuna, drawing on both published and archival resources. What emerges is a story of a label of uncertain origin but wrapped up in competing agendas, the first stage in the history of which culminates in 1962 with its rejection by two of the very people who helped birth it.